2012
DOI: 10.1002/lt.23411
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of liver transplant recipients with hepatitis C and human immunodeficiency virus coinfection

Abstract: BACKGROUND Hepatitis C virus (HCV) is a controversial indication for liver transplantation (LT) in HIV-infected patients due to reportedly poor outcomes. METHODS This prospective U.S. multicenter cohort study compared patient and graft survival in 89 HCV-HIV coinfected versus 2 different controls groups: 235 HCV monoinfected LT controls and all U.S. transplant recipients ≥65 years. RESULTS The 3-year patient and graft survival rates (95% CI) were 60% (47–71%) and 53% (40–64%) in HCV-HIV versus 79% (72–84%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
245
2
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(264 citation statements)
references
References 26 publications
13
245
2
4
Order By: Relevance
“…133 Two prospective studies have shown lower patient survival and higher incidence of acute cellular rejection in HCV and HIV coinfected cohort compared to HCV monoinfected patients. 134,135 FCH and sepsis are the leading causes of death in HCV and HIV coinfected patients. [136][137][138] With the availability of DAA for the treatment of recurrent HCV following liver transplantation, SVR rates have improved in HCV and HIV coinfected patients.…”
Section: Management Of Hcv In Hiv Coinfectionmentioning
confidence: 99%
“…133 Two prospective studies have shown lower patient survival and higher incidence of acute cellular rejection in HCV and HIV coinfected cohort compared to HCV monoinfected patients. 134,135 FCH and sepsis are the leading causes of death in HCV and HIV coinfected patients. [136][137][138] With the availability of DAA for the treatment of recurrent HCV following liver transplantation, SVR rates have improved in HCV and HIV coinfected patients.…”
Section: Management Of Hcv In Hiv Coinfectionmentioning
confidence: 99%
“…Endomyocardial biopsies are performed as in every other transplant patient following local protocols, with a minimum of six biopsies during the first 6 months after transplant and subsequently if clinically indicated. Findings from liver and kidney transplant cohorts seem to confirm that HIVinfected persons are significantly more likely to develop acute rejection than recipients without HIV infection (8,9,33). In fact, most HT recipients with HIV infection listed in Table 2 had rejection episodes.…”
Section: Immunosuppression and Rejectionmentioning
confidence: 90%
“…Although our series is limited in number and very select, the 3-year patient survival rate for HIV/HCV-coinfected patients was similar to the 3-year survival rate for HCV-monoinfected patients and higher than the rate for HIV/HCVcoinfected cases in Terrault et al's series. 1 According to our data, HCV coinfection should not be considered a contraindication for LT in HIV-infected patients. In agreement with our North American colleagues, we believe that the key to successful LT in an HIV setting depends on the accurate selection of patients and donors and the intensive management of drug interactions to prevent acute rejection.…”
Section: To the Editorsmentioning
confidence: 68%
“…The 3-year incidence of treated acute rejection was 1.6-fold higher for HCV/HIV-coinfected patients versus HCVmonoinfected patients (P ¼ 0.02), but the cumulative rates of severe HCV disease (29% versus 23% at 3 years) were not significantly different (P ¼ 0.21). The authors concluded that HCV per se is not a contraindication for LT in patients with HIV, but the selection of recipients and donors and the management of acute rejection strongly influence outcomes.We would like to comment on the results of Terrault et al 1 and report the outcomes of 32 consecutive HIVinfected patients undergoing LT at our center in Udine, Italy (2004-2010. This study protocol was approved by the institutional review committee of the Italian National Transplant Center.…”
mentioning
confidence: 99%